Remote-Sensing Measurements of Wave Breaking at Two Pacific Northwest Jettied Inlets - Rob Holman; Hans Rod Moritz; James McMillan (Journal of Marine Science and Engineering, 2022)
Breaking waves constitute one of the main environmental stressors on coastal structures as well as a leading hazard to navigation in nearshore regions. In this paper, we use camera-based methods to measure wave breaking over two jetty systems in the Pacific Northwest; the North jetty of the Columbia River, Washington state, and the two jetties of Coos Bay, Oregon, as well as over three nearby nearshore dredge disposal areas. Data were collected using the “brightest” images and Argus camera technology over a span of 847 days for the Columbia River and 202 days for Coos Bay. Wave breaking over the Columbia north jetty reached 100% for wave heights greater than 3 m and for tides above mid-tide level and was concentrated on the seaward half of the jetty. For Coos Bay, the south jetty saw substantially more breaking than the north one with the worst overtopping occurring mid-jetty and seeming to be associated with sediment transport through the jetty and into the inlet, as well as possibly the navigation channel. Wave breaking at the Coos Bay inlet mouth was enhanced during ebb flow conditions. Argus imagery analysis showed no evidence of enhanced breaking over any of the three dredge material placement sites.